2018
DOI: 10.1029/2018jg004485
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Drought on Native Southern California Vegetation: Remote Sensing Analysis Using MODIS‐Derived Time Series

Abstract: Ecosystems in Mediterranean climates are adapted to seasonal drought. Multiannual drought, however, may significantly affect Mediterranean ecosystems and, further, may affect their constituent communities in different ways with differences in responses emerging during severe drought and over the course of long‐term climate change. This study investigates the response to recent prolonged drought of two important Mediterranean‐climate vegetation types: chaparral and coastal sage scrub. Their greenness was monito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 57 publications
(76 reference statements)
2
33
0
Order By: Relevance
“…Another remote sensing-based study by Brodrick and Asner (2017) reported a close relationship between sustained canopy water loss and mortality in conifers over the Sierra Nevada mountain range in California. However, the vegetation responses to drought represented by NDVI may vary with vegetation types (e.g., Fensholt et al, 2012;Gamon et al, 1995;Okin et al, 2018;Reed et al, 1994;Vicente-Serrano et al, 2013). However, the vegetation responses to drought represented by NDVI may vary with vegetation types (e.g., Fensholt et al, 2012;Gamon et al, 1995;Okin et al, 2018;Reed et al, 1994;Vicente-Serrano et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another remote sensing-based study by Brodrick and Asner (2017) reported a close relationship between sustained canopy water loss and mortality in conifers over the Sierra Nevada mountain range in California. However, the vegetation responses to drought represented by NDVI may vary with vegetation types (e.g., Fensholt et al, 2012;Gamon et al, 1995;Okin et al, 2018;Reed et al, 1994;Vicente-Serrano et al, 2013). However, the vegetation responses to drought represented by NDVI may vary with vegetation types (e.g., Fensholt et al, 2012;Gamon et al, 1995;Okin et al, 2018;Reed et al, 1994;Vicente-Serrano et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Satellite-derived Normalized Difference Vegetation Index (NDVI) data have long been used to monitor the impacts of drought on vegetation greenness, which is sensitive to soil moisture conditions and precipitation (Gu et al, 2007(Gu et al, , 2008Karnieli et al, 2010;Kogan, 1995;Pettorelli et al, 2005;Reed et al, 1994;Williams et al, 2013). However, the vegetation responses to drought represented by NDVI may vary with vegetation types (e.g., Fensholt et al, 2012;Gamon et al, 1995;Okin et al, 2018;Reed et al, 1994;Vicente-Serrano et al, 2013). Geographically differentiated average climate can also exert influence on the vegetation responses to drought.…”
Section: Introductionmentioning
confidence: 99%
“…Jacobsen and Pratt [116] found that the Southern California shrublands are relatively resilient to short-term high-intensity droughts, but displayed significant dieback and mortality during the recent prolonged drought (2012-2016); they concluded that the highly cavitation-resistant shrubs are the ones most affected by long-term high-intensity drought. This is supported by [50], who argued that the deep-rooting system of chaparrals buffers them from summer drought but makes them particularly vulnerable to multi-year drought, where the soil water stored in the deep layers is reduced by persistent evaporation. Our results further reveal that the chaparral communities seem to be less resilient to climate disturbance than the other vegetation types.…”
Section: Discussionmentioning
confidence: 93%
“…This approach better reflects the regional vegetation distribution than the nearest-neighbor interpolation, and is less affected by data noise and misclassifications [80]. Additionally, a rigorous data quality control was implemented by the California Department of Fish and Wildlife in generating the SWAP database and, thus, it is the "best available" land cover data for California at present [50]. Vegetation cover typical of chaparral is comprised of sclerophyllous, evergreen-leaved shrubs with hard stems and deep roots with a variety of species.…”
Section: Ancillary Gis Datamentioning
confidence: 99%
See 1 more Smart Citation